KEANEKARAGAMN FUNGI MIKORIZA ARBUSKUA (FMA) LAHAN KAMPUS UNIVERSITAS LANCANG KUNING (UNILAK - Ervayenri, Ervayenri (Wahana Forestra: Jurnal Kehutanan, 2020)
Arbuscular mycorrhizal fungi (AMF) are naturally scattered and symbiotic with various tree species, AMF is able to improve plant adaptation to extreme soil conditions. About thirty-seven years Unilak, has been built in Riau Province, precisely in Rumbai Pekanbaru City. How is the existence of FMA on the developed campus land? Is the focus of this paper. Soil sampling for AMF observation refers to the modified ICRAF method. The extraction of AMF spores followed the pour and wet filter method followed by centrifugation techniques. Based on the morphological characteristics of the extracted AMF spores, it was identified to the genus level. The research series showed that the presence of AMF on the Unilak campus area contained 13 types of spores from the genus Acaulospora, Gigaspora, Glomus and Sclerocystis.